Murowany dwór obronny z XVI wieku w Kazanowie Starym, gmina Końskie, województwo kieleckie - Ćwiertak, Edward (Acta Universitatis Lodziensis. Folia Archaeologica, 1997)
In 1982 and 1985 excavations by a group of searchers from the Provincial Center of Archaeology and Preservation in Kielce took place in the village of Kazanów Stary. A hillock (c. 2,5 m high, c. 25 m diameter) hiding relics of the fortified manor house was explored. In the first season of excavation three ditches on the south and the north of the foundation were dug out, and in 1985 four others covering the rest of territory of the hillock (Fig. 2). The works carried out there gave the full plan of the manor house together with an adjacent court. The whole foundation i.e. the manor house and the court surrounded by a stone wall, occupying area of 26x16 m was situated on the north-south axis. The house of a lord had three turrets in its south-west, north-west and north-east comers. The court adjoined the house from the north. The main gate was located on the north curtain of the court wall. A configuration of terrain suggests that the foundation was surrounded by a wet moat of 10-15 m width. However, surveys did not answer the question whether the moat ringed the place from all sides. In the groups of materials fragments of ceramics compose the overwhelming majority (79,4%). Then, there goes glass (14,3%), fragments of iron specimens (2,9%), fragments of animal bones (3,1%). The group of ceramics consists of 499 fragments of vessels and 56 fragments of stove tiles. Only 2 pieces of vessels might date back to the Middle Ages while the others represent features typical for modern ceramics. Therefore, the group of vessels may date from the half of 16th to the 2nd half of 17th century (Plate I). The stove tiles represented at most by the plate type have presumably the same datation. In the group of iron specimens a finding of a cross-bow butt is worth noting. The manor house in Kazanów Stary is a realisation of the ideological program of „a house of a lord” which developed in 16th century. The object unites a typical plan of a dwelling house with a function of protecting dwellers from an attack. The lack of archival information about the manor house makes time of its construction questionable. In this case it can be qualified by archaeological and geneological materials. In the light of this sources the foundation may have been built between 1540-1550 by Marcin Kazanowski (1523-1587). The seat of the Kazanowski family lost its importance during the life-time of Zygmunt (1563-1634) and from the turn of 17th and 18th century up to the present days it has been successively devastated and ruined.